The Constitutional Development And Operations Of The National People’s Congress - Dowdle, Michael W. (Columbia Journal of Asian Law, 1997)
This article is divided into three parts. Part I provides a brief analysis of the NPC’s institutional emergence since 1978. First, it recounts the path of that emergence. Then, it identifies some of the forces behind this emergence, including the receding influence of the CCP, the emergence of more pluralist forces in Chinese society, the articulation of regional interests, and the development of regional people’s congresses. Finally, it argues that both the path of and the various motors behind the NPC’s institutional development strongly evince the presence of an emerging "constitutional consciousness" within China’s political environment. Parts II and III examine the structure and operations of the NPC, respectively. While these two attributes are analyzed separately for the sake of convenience, both are means to the same end: the realization of the NPC’s various constitutional responsibilities. Inter alia, the NPC’s structure and attendant operations reveal a political entity attempting to develop and rationalize its various constitutional roles into a coherent institutional framework within the significant constraints of its political environment.